Fatigue Failure of Alloy Grade P22 Hot Reheat Auxiliary Steam Pipe - Anis Muneerah Shaiful Bahari; Saidatul Akmal Biyamin; Muhammad Hilmi Khairuddin; Ng Guat Peng; Norlia Berahim; Saiful Adilin Shokri; Mohd Hafiz Abdul Ghaffar; Mazmi Yahya; Robiah Ghazali, (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
A leak was discovered in the hot reheat auxiliary pipe. The pipe was found to have a bulging condition and a crack at the base metal area. A circumferential crack was discovered near a repair weld spot on the external surface. The failure was investigated using material characterization techniques, including in-situ replication, glow discharge spectroscopy (GDS), microhardness analysis, optical microscopy, and energy dispersive X-ray spectroscopy (EDX). Based on microstructure analysis, numerous cracks were observed to have initiated at the internal surfaces of the pipe. Most of the cracks were found on the parent metal. The cluster of cracks concentrates on the plane of 0⁰ - 180⁰. Microstructure analysis shows that the cracks are multiple, parallel, mainly transgranular, oxide-filled with branching crack tips. It is thought that the cracking is associated with fatigue and, most likely, high cyclic stress is the key contributory factor. The steam oxide cracked gradually as a result of the cyclic stress. As more metal surface was exposed, new oxide formed, causing cracks to propagate into the metal as this process was repeated due to cyclic loading.